Church proliferation and immorality in Nigeria: Interrogating the paradox - Onah, Nkechi G. (HTS teologiese studies, 2021)
In Nigeria, there is an upsurge in the number of churches. This church proliferation in Nigeria has given rise to the founding of a variety of denominations whilst moral decadence thrives. This article therefore examines the issue of proliferation of churches, its causes and effects on Christianity and the Nigerian society at large. Data for the study were drawn from journals, books and other relevant materials. Employing descriptive narrative approach, this article indicates that the reasons for churches’ proliferation include God’s calling, unemployment, excessive desire for wealth or greed and leadership tussles. The article argues that despite the positive effects of proliferation of churches, which include socio-economic development, spiritual awakening and evangelism, it also has negative effects such as lack of quality Christian teachings, noise pollution, unhealthy competition and family disintegration. The article suggests that the pastors and ministers of God should receive good training from theological schools for proper interpretation of the Bible and better dissemination of the gospel. They should show good examples to their members and the society at large. It further suggests that noise regulation laws in the country should be enforced.Contribution: The article examines the issue of proliferation of churches in Nigerian society. In Nigeria, churches are opened in every part of society but Christian religious worship is not being practiced in its true form. Notwithstanding the geometrical increase in churches, other vices have remained unabated in the country.